Design optimization and manufacture of permanent magnet synchronous motor for new energy vehicle. (November 2022) - Ye, Weiwen; Liu, Yongqiu; Wu, Guangming; Wu, Qifei; Chen, Zhensen; Chen, Zhensheng; Li, Zhenhua; Cao, Zhijie
Abstract: With the lack of energy and the amazing development of the automobile industry, new energy electric vehicles are bound to become one of the important means of transportation in the future Permanent magnet synchronous motor drive is the most critical power component in new energy vehicles, and its performance determines the driving quality of the whole vehicle This paper designs the circulating cooling system according to the requirements of motor temperature threshold The thermal simulation analysis of the designed heat dissipation structure is carried out Compare the test value with the simulation design value Finally, according to the simulation results, the motor parts are numerically processed and assembled The designed electric oil cooled permanent magnet synchronous motor provides strong technical support for the upgrading and transformation of relevant industries, increases the core competitiveness of enterprises in the field of new energy vehicle motors, breaks the technical blockade and shortens the gap with powerful automobile manufacturing countries.